Pengolahan Bahan Organik Menjadi Produk Makanan Kucing “MiMeow” - Wirren Chang; Edy Yulianto Putra; Agnes Doraresta Khatarina Tokan; Delfina Muthia Sabella; Dewi Dewi; Mardiana Ng; Serina Serina (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Stray cats are usually easily infected with disease because they don't have owners to take care of them, wild cats generally take food in the trash which is definitely not suitable for consumption because it's not only dirty but the food in the trash doesn't contain enough nutrients. This is what made the researchers come up with the idea to produce a healthy and nutritious food for wild cats and domestic cats named "MiMeow". The food produced by the researchers is in the form of wet food. The purpose of this researcher's idea is to do an innovative food business dan also invite people who have bought and used MiMeow products to participate in donating and caring for stray cats. The method used in carrying out cat food production activities is by distributing questionnaires. The results of this study will explain the plans and concepts of MiMeow.